Evaluation of a trial‐based interview‐informed synthesized contingency analysis. Issue 2 (26th July 2019) - Curtis, Kaitlin S.; Forck, Kara L.; Boyle, Megan A.; Fudge, Brittany M.; Speake, Heather N.; Pauls, Benjamin P.
Abstract : We evaluated the viability of an interview‐informed synthesized‐contingency analysis (IISCA) conducted in a trial‐based format with 3 children with autism spectrum disorders who engaged in problem behavior. We compared results to those from typical trial‐based and traditional functional analyses and found high degrees of correspondence. The trial‐based IISCA format took the least amount of time to conduct and was associated with the lowest frequencies of problem behavior. Results are discussed in terms of merits of each of the 3 types of functional analysis arrangements and directions for future research.